Forecasting Interest Rate of Bank Indonesia Certificate Based on Multivariate Fuzzy Time Series Data - Agus Maman Abadi; Subanar Subanar; Widodo Widodo; Samsubar Saleh (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2010)
The aim of this research is to establish a model for forecasting interest rate of Bank Indonesia Certificate (BIC)based on six-factors one-order fuzzy time series data where the main factor is interest rate of BIC and thesecondary factors are interest rate of deposit, exchange rate, deposit supply, inflation rate and money supply.Steps to forecasting interest rate of BIC are based on Wang’s method. The result of this research is thatprediction of interest rate of BIC using multivariate fuzzy time series model has higher accuracy than that usingneural network method with average forecasting error 3.1256% and MSE value = 0.2699.